The Role of The Bernard Farmers Group in The Performance of Chili Farming in Pangalengan District, Bandung Regency - Audri Aulia Masita Dewi; Dwi Rachmina; Yanti Nuraeni Muflikh (Universitas Muhammadiyah Malang, 2025)
Farmer groups can be a forum for acquiring knowledge and solving agricultural problems. One farmer group that helps solve problems and empower farmers is the Bernard Farmer Group in Warnasari Village, Pangalengan District, Bandung Regency. The Bernard Farmer Group assists its member farmers in chili farming activities, including marketing. However, the dynamics of the Bernard Farmers Group's role have declined since 2023. Does this decline in role affect the performance of the cayenne pepper farming business managed by members of the Bernard Farmers Group? This study aims to analyze the role of the Bernard Farmers Group in the performance of the Cayenne Pepper Farming business. The performance of the cayenne pepper farming business is measured by analyzing the income of member farmers before and after the change in the role of the Bernard Farmers Group. The period before the change in role is referred to as period 1, and the period after the role decreased is referred to as period 2. The sampling technique used is a census, which is a sampling technique where all members of the population are used as samples. The sample size is 20 farmers who are members of the Bernard Farmer Group. To see the difference in farmer income after the change in the role of the Bernard Farmer Group, a paired t-test is used. The role of the Bernard Farmer Group included training or assistance by the group, collaboration between farmers, ease of marketing production through the Bernard Farmer Group, and the implementation of weekly or monthly meetings. In the second period, these roles declined compared to the previous period. The decline in roles resulted in a decrease in the performance of chili farming, as seen from a 6.19% decrease in income and a 7.19% decrease in R/C ratio.